Application of artificial intelligence techniques for the verification of pile capacity at construction site: A review - Sai Hin, Lai; Chia Yu, Huat; Danial Jahed, Armaghani; Ehsan, Momani (Elsevier, 2023)
In the construction industry, piling is part of foundation system that supports the constructed structures. There are various types of piles that can be designed and constructed such as bored piles, micropiles, spun piles, and pre-cast reinforced concrete square piles. Ground conditions and costs are two main factors to decide the piling system to adopt in the construction. Prior to the construction of piling, theoretical design of the piles is required to identify the capacity of pile based on the subsurface investigation works information.